ANALISIS BALANCED SCORECARD AGRIBISNIS JAMBU BIJI MERAH - Maimunah, Maimunah; Kristiawan, Kristiawan (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2020)
This study aims to see the extent to which red guava agribusiness performance in supporting business objectives, namely increasing income. The study was conducted on red guava farming in the District of Palang, Tuban Regency using the survey method. Sampling is done purposively, using balanced scorecard analysis to assess its performance. Data retrieval used to support analysis is data about income and sales (financial perspective), production costs and the number of products produced (customer perspective), how many sales innovations are carried out (internal business process perspective) and data on how many financial institutions are related in business development (learning perspective). The results of the study show that financial and customer perspectives have reached the achievement target, while the internal business process and learning perspective needs to be improved.